A prolyl oligopeptidase inhibitor reduces tau pathology in cellular models and in mice with tauopathy - Eteläinen, Tony; Silva, M. Catarina; Uhari-Väänänen, Johanna K.; De Lorenzo, Francesca; Jäntti, Maria H.; Cui, Hengjing; Chavero-Pieres, Marta; Kilpeläinen, Tommi; Mechtler, Christina; Svarcbahs, Reinis; Seppälä, Erin; Savinainen, Juha R.; et al. (Science translational medicine, 2023)
Tauopathies are neurodegenerative diseases that are characterized by accumulation of hyperphosphorylated tau protein, higher-order aggregates, and tau filaments. Protein phosphatase 2A (PP2A) is a major tau dephosphorylating phosphatase, and a decrease in its activity has been demonstrated in tauopathies, including Alzheimer’s disease. Prolyl oligopeptidase is a serine protease that is associated with neurodegeneration, and its inhibition normalizes PP2A activity without toxicity under pathological conditions. Here, we assessed whether prolyl oligopeptidase inhibition could protect against tau-mediated toxicity in cellular models in vitro and in the PS19 transgenic mouse model of tauopathy carrying the human tau-P301S mutation. We show that inhibition of prolyl oligopeptidase with the inhibitor KYP-2047 reduced tau aggregation in tau-transfected HEK-293 cells and N2A cells as well as in human iPSC-derived neurons carrying either the P301L or tau-A152T mutation. Treatment with KYP-2047 resulted in increased PP2A activity and activation of autophagic flux in HEK-293 cells and N2A cells and in patient-derived iNeurons, as indicated by changes in autophagosome and autophagy receptor markers; this contributed to clearance of insoluble tau. Furthermore, treatment of PS19 transgenic mice for 1 month with KYP-2047 reduced tau burden in the brain and cerebrospinal fluid and slowed cognitive decline according to several behavioral tests. In addition, a reduction in an oxidative stress marker was seen in mouse brains after KYP-2047 treatment. This study suggests that inhibition of prolyl oligopeptidase could help to ameliorate tau-dependent neurodegeneration.
Gesehen am 05.07.2023